2020
DOI: 10.24287/1726-1708-2020-19-3-12-16
|View full text |Cite
|
Sign up to set email alerts
|

Description of health related quality of life of children and adolescents with hemophilia from India

Abstract: Hemophilia is a genetic disease that impairs quality of life due to its chronicity of nature where the individual will experience spontaneous bleeding or bleeding after an injury which requires frequent visits to the hospital for treatment. The objective of this study was to find the Health-related quality of life (HRQoL) of children and adolescents with moderate and severe hemophilia between 6 years and 16 years using the Haemo-QoL questionnaire. A prospective survey was carried out among 107 children and ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 15 publications
3
17
2
Order By: Relevance
“…Table 1 [ 6 , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] ] provides a brief description of each included study and an outline of the characteristics of each study population. The 29 included studies reported on 6 distinct instruments that were used to measure HRQoL in 2346 children and adolescents with hemophilia A.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 1 [ 6 , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] ] provides a brief description of each included study and an outline of the characteristics of each study population. The 29 included studies reported on 6 distinct instruments that were used to measure HRQoL in 2346 children and adolescents with hemophilia A.…”
Section: Resultsmentioning
confidence: 99%
“… Dsouza et al. [ 35 ]/2020/India/Peer-reviewed journal article Cross-sectional, no treatment comparison 107 6-16 y Distribution according to socioeconomic class: 18.7% poor class, 67.3% lower middle class, and 14.0% upper middle class. 89.7% 100% 0.0% FVIII Proportion on prophylaxis not reported Haemo-QoL Long Form Kids II (8-12 y) and III (13-16 y).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations